2012
DOI: 10.4269/ajtmh.2012.11-0516
|View full text |Cite
|
Sign up to set email alerts
|

Training Laboratory Technicians from the Ethiopian Periphery in the MODS Technique Enables Rapid and Low-Cost Diagnosis of Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB) is a leading cause of morbidity and mortality and is frequently complicated by emergence of drug-resistant strains. Diagnosis of TB in developing countries is often based on the relatively insensitive acid-fast staining that does not enable susceptibility profiling. Microscopic observation drug susceptibility assay (MODS) is an inexpensive, simple method that enables rapid TB culture coupled with susceptibility testing. A 3-week MODS training of three Ethiopian laboratory technicians was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…WHO has endorsed the assay for DST but has not recommended its implementation at district level. However, it has been shown that technicians from peripheral health centre laboratories without previous experience in TB cultures can learn MODS technique in 3 weeks . Published numbers for the cost per test for the MODS assay have varied, ranging from as little as 0.72 USD to 7.31 USD including labour costs, fixed costs and DST .…”
Section: Introductionmentioning
confidence: 99%
“…WHO has endorsed the assay for DST but has not recommended its implementation at district level. However, it has been shown that technicians from peripheral health centre laboratories without previous experience in TB cultures can learn MODS technique in 3 weeks . Published numbers for the cost per test for the MODS assay have varied, ranging from as little as 0.72 USD to 7.31 USD including labour costs, fixed costs and DST .…”
Section: Introductionmentioning
confidence: 99%
“…This however can be remedied with proper training. There are reports on MODS training of laboratory staff outside of research laboratories and results are encouraging [22,23]. Furthermore, other potential challenges include medical technologist time requirement and the need for detailed attention to laboratory procedures to prevent contamination.…”
Section: Limitationmentioning
confidence: 99%
“…Courses of this type are common in the developing world and may be funded by local or national governments or non-governmental organizations. [1][2][3] The impact of short courses on veterinary paraprofessionals in developing nations is not fully known, although limited studies of such courses have found an overall positive impact on the activities of trainees. 4,5 The success of short intensive training courses in preparedness for highly pathogenic avian influenza led investigators to conclude that the same approach could be used to develop educational materials for other diseases that pose a threat to animal agriculture.…”
Section: Introductionmentioning
confidence: 99%